Prevalence of Bovine Genital Campylobacteriosis, Associated Risk Factors and Spatial Distribution in Spanish Beef Cattle Based on Veterinary Laboratory Database Records - Pena-Fernández, Nerea; Cano-Terriza, David; García-Bocanegra, Ignacio; Horcajo, Pilar; Vázquez-Arbaizar, Patricia; Cleofé-Resta, Darío; Pérez-Arroyo, Bárbara; Ortega-Mora, Luis M.; Collantes-Fernández, Esther (Frontiers in Veterinary Science, 2021)
Bovine genital campylobacteriosis (BGC) is a sexually transmitted disease that causes early reproductive failure in natural breeding cattle that are managed extensively. The aim of this study was to assess the BGC prevalence in Spain from 2011 to 2019 using data collected cross-sectionally from the diagnostic reports issued by the SALUVET veterinary diagnostic laboratory from a total of 5182 breeding bulls from 1950 herds managed under “dehesa” systems (large herds within fenced pastures and all-year breeding season) or mountain systems (smaller herds with seasonal breeding management and grazing in communal mountain pastures). Infection was detected by PCR in 7.7% and 12.2% of the bulls and herds tested, respectively. The “dehesa” herd management system (OR= 2.078, P= <0.001, 95% CI= 1.55– 1.77), bovine trichomonosis status of the herd (OR=1.606, P=0.004, 95% CI= 1.15 – 2.22), and bulls ≥ 3 years old (OR= 1.392, P= 0.04, 95% CI= 1.01 – 1.92) were identified as risk factors associated with Campylobacter fetus venerealis infection. We also studied the high-risk areas for circulation of the infection in extensive beef cattle herds in Spain, showing four significant clusters in “dehesa” areas in the south-western provinces of the country and a fifth cluster located in a mountain area in northern Spain. The results obtained in the present study indicate that BGC is endemic and widely distributed in Spanish beef herds. Specifically, “dehesa” herds are at greater risk for introduction of Cfv based on relatively high local prevalence of the infection and the use of specific management practices.